Analisis Hubungan Kemitraan antara Kurir dan Perusahaan pada Masa Pandemi Covid-19 Ditinjau dari Doktrin Undue Influence - Yolanda Simbolon (Darma Cendika Catholic University, 2022)
This article explores the potential modern exploitation of the partnership between couriers and delivery companies. This research is normative legal research. The author used data from the literature and a survey of 37 couriers from 14 different companies. Of the 37 couriers who filled out the survey, in-depth interviews were conducted on 7 couriers from 6 different companies. The results suggested that the practice of Undue Influence can occur when the courier is economically or psychologically powerless to bind in a partnership agreement with the company. During the Covid-19 pandemic, couriers have a much weaker economic and psychological position than the company. The company uses its special circumstances to establish policies unilaterally and makes a “take it or leave it” offer to the courier. Moreover, the relationship between the courier and the delivery company that is applied is not an industrial relationship, so it is not subject to the provisions of the legislation concerning manpower. Consequently, the provisions in the partnership agreement do not have a safety net for couriers and tend to only side with the company.